The Influence of Residuals Combining Temperature and Reaction Time on Calcium Phosphate Transformation in a Precipitation Process - Farnaz Ghajeri; Klaus Leifer; Anders Larsson; Håkan Engqvist; Wei Xia (Journal of Functional Biomaterials, 2022)
Precipitation is one of the most common processes to synthesize hydroxyapatite, which is the human body’s mineral forming bone and teeth, and the golden bioceramic material for bone repair. Generally, the washing step is important in the precipitation method to remove the residuals in solution and to stabilize the phase transformation. However, the influence of residuals in combination with the reaction temperature and time, on calcium phosphate formation, is not well studied. This could help us with a better understanding of the typical synthesis process. We used a fixed starting ion concentration and pH in our study and did not adjust it during the reaction. XRD, FTIR, ICP-OES, and SEM have been used to analyze the samples. The results showed that combining residuals with both reaction temperature and time can significantly influence calcium phosphate formation and transformation. Dicalcium phosphate dihydrate formation and transformation are sensitive to temperature. Increasing temperature (60 °C) can inhibit the formation of acidic calcium phosphate or transform it to other phases, and further the particle size. It was also observed that high reaction temperature (60 °C) results in higher precipitation efficiency than room temperature. A low ion concentration combining reaction temperature and time could still significantly influence the calcium phosphate transformation during the drying.